Urban sensation of colonial Malaya and Singapore: the flaneur's sensory experiences in Chan Ling Yap's new beginnings - Amran, Nurul Atiqah (Penerbit Universiti Kebangsaan Malaysia,National University of Malaysia Press, 2024)
Urban sensations are the grounding force that binds the ‘flâneur’ to the streets. A ‘flâneur’ is a French term that describes a casual wanderer and a keen observer of society, culture, and the environment, often found in urban settings. The term originates from the 19th-century Parisian context and is associated with the literature of Charles Baudelaire and the idea of modernity. This study applies the theoretical approach of psychogeography, giving a heuristic point of view to present an analysis of the sensory urban experience that allows the ‘flâneur’ to move sensibly in the fictional urban labyrinth. Drawing from Boutin’s work, which addresses how the ‘flâneur’ transforms the city into a sensory-rich environment, this study delves into the visionary, auditory, and tactile experiences that anchor the ‘flâneur’ in Chan Ling Yap’s New Beginnings to the streets of the British colonial rule in Malaya and Singapore. It also explores the protagonist’s struggle to navigate and confront the alluring yet perilous attractions of the urban landscape. The aim is to uncover deeper insights into his internal conflicts and the implications for urban residents' interactions with their environment. The findings show that the protagonist's engagement with the urban environment demonstrates the pleasure of city wandering and the wisdom of 'flânerie' is not exclusive to the privileged but can also empower individuals from less privileged backgrounds as he adeptly navigates and interprets the city to elevate his societal standing and achieve his goals.